Turkey's foreign policy towards the middle east. - DEMIR, YDRIS (CAMBRIDGE SCHOLARS PUBLIS, 2017)
This book investigates the effects of the Arab Spring on Turkish foreign policy using a multidimensional approach that draws on a wide range of disciplines from international relations to sociology and economics. The demands for democracy that began in Tunisia, when Mohamed Bouazizi set himself on fire in 2010, rapidly spread across the Arab Middle East and Northern Africa. In countries dominated by authoritarian regimes, a freedom and sovereignty movement led by middle-class urbanites changed the quality of politics in the region. The focus and dynamics of the Arab Spring varied across countri.